2021
DOI: 10.3390/su132413608
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Irrigation Water Requirement to Climate Change in Arid and Semi-Arid Regions towards Sustainable Management of Water Resources

Abstract: This study aimed to assess the spatiotemporal sensitivity of the net irrigation water requirement (NIWR) to changes in climate, for sixteen crops widely cultivated in four irrigation projects located in arid and semi-arid regions of Iraq. Using LARS-WG and five GCMs, the minimum and maximum temperature and precipitation were projected for three periods from 2021–2080 with 20-year steps (P1, P2, and P3) under representative concentration pathways (RCPs) 2.6, 4.5, and 8.5. Weather data available for a reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…The results of projected Tmin and Tmax indicated that winter is accelerated towards warming more than summer. These results agree with Saeed et al [49] Furthermore, according to the analysis presented by Zhang et al [50], the results showed that temperature increased in winter at a rate compared with the increase in summer for MENA from 1950-2003.…”
Section: Future Trends In Climate Variablessupporting
confidence: 91%
“…The results of projected Tmin and Tmax indicated that winter is accelerated towards warming more than summer. These results agree with Saeed et al [49] Furthermore, according to the analysis presented by Zhang et al [50], the results showed that temperature increased in winter at a rate compared with the increase in summer for MENA from 1950-2003.…”
Section: Future Trends In Climate Variablessupporting
confidence: 91%
“…Although many synergistic side effects are possible, semi-arid and arid regions are predicted to have the most potential. Here, intense solar radiation and associated water losses frequently have a negative impact on agricultural growth [10]. In PV installations, it has been demonstrated that water consumption efficiency rises underneath the panels; similar outcomes have been seen in APV systems.These results become even more relevant as future climate change is expected to lead to increased demand for irrigation water [11].…”
Section: Introductionmentioning
confidence: 79%
“…Ea is the efficiency of irrigation, and Lr is a requirement of leaching (mm), which is calculated by Lr = f × NIWR, where f ranges from (five to twelve ) percent upon available soil salinity [15]…”
Section: The Cropwat Modelmentioning
confidence: 99%
“…In Iraq, a few studies evaluated the effect of climate change on the irrigation water requirements of crops. Saeed et al [15] evaluate the spatiotemporal sensitivity of the net irrigation water requirement (NIWR) under climate changes for four irrigation projects located in arid and semi-arid regions of Iraq for North Jazeera Irrigation Project (NJIP), Kirkuk Irrigation Project (KRIP), Upper Khalis Irrigation Project (UKIP), and Dalmaj Irrigation (DLIP), respectively, So This study is considered the first study that determines the climate changes effects on net irrigation water requirements and crop productivity by CROPWAT and machine learning in Iraq ( AL-Najaf governorate) under future climate change scenarios. Three climate change scenarios were utilized to estimate future climate data (RCP2.5, RCP 6, and RCP8.5).…”
Section: Introductionmentioning
confidence: 99%